Type simple house walled CEB which efficient heat energy and embodied energy in Indonesia - Totok Noerwasito, Vincentius (IPTEK Journal of Proceedings Series, 2017)
Efficient energy on heat energy and embodied energy in a simple house type in Indonesia needs to be observed. The type of house is very closely linked with the building area. It is necessary to know in order to determine the type of house by developers or for the government in terms of the energy. This energy efficiency is important because energy is a world problem that must be saved. The buildings in this study using Compressed Earth Block (CEB) wall material. CEB is a low-energy building materials and local material. This material is a type of brick, but not through the process of burning. The research problem is the type of house which one has energy efficient? Because it is not always type with a small area will have energy efficient. The method used was the optimization of the heat energy in this case the cooling load with embodied energy. The research variables was the building floor area is reflected in the type of building. Cooling load in a building was calculated for a year, simulating calculations of the cooling load performed by software Archipak. While the embodied energy calculations using the standard embodied energy per unit. The results showed that the type of building optimal heat energy and embodied energy is a type of building 70 or a building type with the largest area. Building that has a small embodied energy will produce heat energy which is small as well.